THE PROBLEM OF YOUTH INVOLVEMENT IN THE MUSEUM PRODUCT CONSUMPTION - A. Timokhovich; S. Filenko (Вестник университета)
The issues of youth involvement in the consumption of cultural product have been examined. The analysis of theoretical approaches to the construction of models of involvement has been carried out. The models and technologies of consumer engagement on the example of museum grounds have been considered. An engagement model has been developed. The main results of an empirical research, affecting the issues of the study of technologies involving young people in the consumption of a museum product have been described. The recommendations on the application of technologies involving in the consumption of the museum product have been provided.